2017
DOI: 10.1093/mnras/stx393
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a stellar cusp by a dark matter cusp in a low-mass compact ultrafaint dwarf galaxy

Abstract: Recent observations have been discovering new ultra-faint dwarf galaxies as small as ∼ 20 pc in half-light radius and ∼ 3 km s −1 in line-of-sight velocity dispersion. In these galaxies, dynamical friction on a star against dark matter can be significant and alter their stellar density distribution. The effect can strongly depend on a central density profile of dark matter, i.e. cusp or core. In this study, I perform computations using a classical and a modern analytic formulae and N -body simulations to study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…We strongly endorse the development of novel ways to estimate the density profile of small galaxies with photometry alone, as proposed by Ref. [248].…”
Section: Observationssupporting
confidence: 57%
See 2 more Smart Citations
“…We strongly endorse the development of novel ways to estimate the density profile of small galaxies with photometry alone, as proposed by Ref. [248].…”
Section: Observationssupporting
confidence: 57%
“…This is on account of their paucity of stars (but see Refs. [247,248] for ideas on photometric estimates of density profiles). For these systems, we are in the near-term limited to estimates of the mean density within the half-light radius of each system.…”
Section: Cusp/core Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DFT studies have shifted their focus from GCs to DF on stars. Using analytical approaches, as in Hernandez [143], or numerical techniques, in Inoue [144], on ultra-faint satellite galaxies of our galaxy, was shown that DM fractions imply DFT for the stars themselves and are incompatible with cusped dark matter haloes, at these tiny scales, out of reach of SNF models, and even maybe of DFBC solutions.…”
Section: Exposition Of the Cusp/core Problemmentioning
confidence: 80%
“…Recently, DFT studies have shifted their focus from GCs to DF on stars. Using analytical approaches, as in Hernandez [144], or numerical techniques, in Inoue [145], on ultra-faint satellite galaxies of our galaxy, was shown that DM fractions imply DFT for the stars themselves and are incompatible with cusped dark matter haloes, at these tiny scales, out of reach of SNF models, and even maybe of DFBC solutions.…”
mentioning
confidence: 80%